Diagnostic lymph node pathology - Ashton-Key, Margaret; q; Wright, Penny; Taylor and Francis (Boca Raton, FL : CRC Press, an imprint of Taylor and Francis, 2016)
Diagnostic Lymph Node Pathology presents a logical and systematic approach to lymph node biopsies and guides general pathologists and haematopathologists alike through the maze of differential diagnoses, enabling them to reach an accurate diagnosis.
chapter 1 Handling of lymph node biopsies, diagnostic procedures and recognition of lymphnode patterns -- chapter 2 Normal/reactive lymph nodes: Structure and cells -- chapter 3 Reactive and infective lymphadenopathy -- chapter 4 Precursor B- and T-cell lymphomas -- chapter 5 Mature B-cell lymphomas -- chapter 6 T-cell lymphomas -- chapter 7 Immunodeficiency-associated lymphoproliferative disorders -- chapter 8 Hodgkin lymphoma -- chapter 9 Histiocytic and dendritic cell neoplasms, mastocytosis and myeloid sarcoma -- chapter 10 Non-haematolymphoid tumours of lymph nodes -- chapter 11 Needle (trephine) core biopsies of lymph nodes.
Keywords: MEDICAL / Pathology; SCIENCE / Chemistry / General; Ganglions lymphatiques -- Maladies -- Diagnostic; Ganglions lymphatiques -- Maladies; x; x; x; x; x; Lymphatic Diseases -- diagnosis